2014
DOI: 10.1038/ncomms6732
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 is essential for the vascular response to environmental cold exposure

Abstract: The cold-induced vascular response, consisting of vasoconstriction followed by vasodilatation, is critical for protecting the cutaneous tissues against cold injury. Whilst this physiological reflex response is historic knowledge, the mechanisms involved are unclear. Here by using a murine model of local environmental cold exposure, we show that TRPA1 acts as a primary vascular cold sensor, as determined through TRPA1 pharmacological antagonism or gene deletion. The initial cold-induced vasoconstriction is medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 68 publications
(113 reference statements)
2
151
0
Order By: Relevance
“…Because TRPA1 antagonists are not yet available for human use, we were not able to test the specificity of the response to CA for TRPA1 in humans. However, extensive preclinical experiments support this specificity and currently no evidence for species differences in CA sensitivity has been reported [12,32,33]. In line with other DBF models such as the capsaicin model, one can assume that several factors such as sex, age and body site can play a role in the response to CA.…”
Section: Figurementioning
confidence: 84%
See 2 more Smart Citations
“…Because TRPA1 antagonists are not yet available for human use, we were not able to test the specificity of the response to CA for TRPA1 in humans. However, extensive preclinical experiments support this specificity and currently no evidence for species differences in CA sensitivity has been reported [12,32,33]. In line with other DBF models such as the capsaicin model, one can assume that several factors such as sex, age and body site can play a role in the response to CA.…”
Section: Figurementioning
confidence: 84%
“…Another unresolved question is whether the DBF response observed is due to activation of neuronal and/or vascular TRPA1. Based on preclinical findings of Aubdool et al, it seems that neuronal TRPA1 is activated, which in turn causes the release of several neuropeptides including CGRP, Substance P and prostaglandins, and are most likely to play an important role in the neurogenic inflammation reaction [12,[32][33][34]. Therefore, future research questions still to be looked into are: (1) which secondary messengers are involved in the DBF response after …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…receptors. 33,34 Previous studies have demonstrated that sympathetic stimulation expands the HSC population via b2-adrenergic receptor activation, 10 whereas b3-adrenergic receptor activation triggers HSC/progenitor mobilization by decreasing stromal cellderived factor-1 (or CXC chemokine ligand 12) messenger RNA levels in BM stromal cells. 31 Activation of the b2-adrenergic receptor is involved in the isoproterenol-induced proliferation of erythroid progenitor cells, 35 whereas a1-adrenergic receptor activation mediates the stimulatory effect of noradrenergic regulation on lymphohematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Full-field laser perfusion imaging [17] (LPI) (Moor Instruments Ltd., Devon, UK) was used to assess MSA blood perfusion by analyzing video frame rate images of blood flow. Briefly, the exposed MSAs of anesthetized rats were imaged by a two-dimensional laser speckle contrast imaging system, as mentioned above.…”
Section: Methodsmentioning
confidence: 99%